Patient care after heart transplantation - a case study - Majchrowicz, Bożena (Journal of Education, Health and Sport, 2022)
Heart transplantation is a recognized and effective method of treating end-stage heart failure. Complicated heart transplant surgery carries a high surgical risk as well as complications that are dangerous to life and health. Transplantation is a life-saving opportunity for patients who have run out of alternative treatments. Patients with heart transplants face many physical and psychological problems every day. The aim of the work was to discuss the care problems of a patient 3.5 years after the heart transplantation procedure. Material and methods: The study used a research method - an individual case study, in which the interview technique, observation, analysis of medical documentation and measurement of vital parameters were used. Results: After the interview, observation and analysis of medical records and as a result of the measurements made, the patient was diagnosed with nursing problems, including such as: increased susceptibility to infections that may pose a serious threat to the life and health of the patient caused by the weakening of the immune system by immunosuppression, anxiety and fear related to the risk of rejection of a transplanted organ and mood instability resulting from uncertain health situation and the effects of immunosuppressive drugs, physical limitations related to with previous operations. Conclusions: Despite the passage of time, the patient after heart transplantation still feels the fear of a sudden deterioration of his health, the occurrence of side effects of the implemented treatment, and to the greatest extent his organism rejects the transplanted organ. Educating the patient, caring for it and keeping track of his health condition makes him feel more confident and at ease. The quality of life of the patient after transplantation can be significantly improved thanks to discipline and properly conducted self-care and self-care.